Geochemical indicators: studies in the Southwest Atlantic Ocean - Santos, Rosangela Felicio dos (2024)
Concerning the South Atlantic Ocean, few studies concentrate on the geochemical investigation of sediments, with focus on understanding the relationships between geochemical signatures, sedimentary sources and oceanic circulation systems. This work used 77 surface sediment samples collected in the Campos, Santos, Pelotas, and Punta del Este basins, between 200 and 1200 meters below the sea surface, and 67 surface sediment samples collected in the Paraíba do Sul Basin (continental, estuarine and shallow marine samples). Samples were collected with box-corers. The first two centimeters underwent Total Digestion and were analyzed by Inductively Coupled Plasma - Optical Emission Spectrometry (ICPOES). The major objectives of this work were: 1) contribute to the understanding of terminologies related to geochemical indicators, and 2) apply proxies, tracers, and other indicators to the four marginal basins in the study area, in order to identify regional signatures of these basins. The application of proxies, tracers and other indicators took place on three fronts: i) application of a tracer (εNd) and, mainly, of metal/metal ratios in the Alpha Crucis Carbonate Ridge (ACCR) region, in the Santos Basin, the result of a work carried out together with researchers from the BiOil project; ii) application of the Ba(excess) productivity proxy in the four marginal basins of the study area, using an indirect analysis method; and iii) application of metal/metal ratios and enrichment factors in the four marginal basins, with a more detained focus on the use of the Discriminant Analysis and the Principal Component Analysis. In all three cases, the interpretation of the results indicated by the geochemical indicators was based on aspects associated with the dominant circulation system in the upper and middle slope portion of the study area, with emphasis on the action of the Brazil Current, the Intermediate Western Boundary Current, which transports recirculated Antarctic Intermediate Water (AAIW), the Malvinas Current, which transports AAIW, and the presence of two potential sources of sedimentary material to the study area, the Paraíba do Sul and the Río de la Plata basins. The application of geochemical indicators found in the literature, the use of statistical tools to identify indicators of interest, and the attempted correspondence between geochemical signatures and sediment sources and depositional areas illustrate the effort to implement sediment tracing and fingerprinting methods to contribute to the refinement of existing source-to-sink models for the area.